ANALYSIS OF PUMP CAPACITY AT THE KARTINI V PUMP HOUSE IN CENTRAL JAKARTA - Imamuddin, Mohammad; Mahdiani, Nila Sekar (International Journal of Civil Engineering and Infrastructure, 2024)
Kartini Volume Pump House is located at Jalan Kartini Raya Simpang Jalan Kartini V, RT. 01 RW. 04, Kartini Village, Sawah Besar District, Central Jakarta, Special Capital Region Of Jakarta, 10750. The geographical location of the pump is located at 6°09'14.4"S 106°50'08.2" E. In the area around the Kartini Volume Pump House, flooding is rare even though the rain that falls has a high rainfall intensity. Despite these conditions, flooding is rare. In the event of a flood, the flood does not last long and will slowly recede after the rain has stopped. This is because the pump in the Kartini Volume Pump House is still functioning properly and the channel capacity is still sufficient. Flooding in the area is caused by narrowing due to garbage in the channel. Using BMKG Kemayoran rainfall data from 2014 to 2023 and the Pearson III Log method, the maximum rainfall intensity of 567.7745 mm/hour with a maximum planned rain discharge of 1.219 m3/second and an existing channel discharge of 15.793 m3/second. The pump capacity in the Kartini Volume Pump House is 2,682 m3/ second with a drain time of 1 hour. The existing pump capacity of the pump gate in the Kartini Volume Pump House is 1 x 2 m3/second and the pump house is 2 x 0.5 m3 / second is still able to accommodate rain discharge in the area.